Menelaah Problematika Kajian Semantik Historis Bahasa Arab di Era Modern - Fikri alhamdi; Hadi, Syofyan; Firdaus, Salsabila (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2025)
This study examines the challenges of historical semantics research in the Arabic language in the modern era. While historical semantics investigates the evolution of word meanings over time, existing literature often overlooks the complex social, political, and religious factors influencing these changes, especially within Arabic. The gap lies in limited integration of socio-political contexts and contemporary linguistic shifts in semantic analysis. This research aims to fill that gap by analyzing semantic changes in Arabic words through both synchronic and diachronic approaches, emphasizing the socio-cultural and religious dynamics involved. A qualitative method combining document analysis and semantic theory review was employed to trace semantic shifts and identify key problematics. The study reveals that modern influences such as colonialism, digitalization, and ideological conflicts significantly affect meaning transformations, posing methodological and ethical challenges for researchers. Findings highlight that the reinterpretation of key terms often reflects broader socio-political struggles and cultural negotiations. The study concludes that a nuanced, context-aware approach is essential for accurate semantic historical analysis of Arabic, balancing respect for traditional meanings with recognition of evolving usages. This contributes to a deeper understanding of language dynamics and offers a framework for future semantic research in Arabic and other languages with rich historical backgrounds